2020
DOI: 10.1042/bsr20200552
|View full text |Cite
|
Sign up to set email alerts
|

Calpain-2 participates in the process of calpain-1 inactivation

Abstract: Calpain-1 and calpain-2 are highly structurally similar isoforms of calpain. The calpains, a family of intracellular cysteine proteases, cleave their substrates at specific sites, thus modifying their properties such as function or activity. These isoforms have long been considered to function in a redundant or complementary manner, as they are both ubiquitously expressed and activated in a Ca2+-dependent manner. However, studies using isoform-specific knockout and knockdown strategies revealed that each calpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…Furthermore, the calpain activity assay was performed on live retinal explants over a duration of 6 h, whereas calpain-2 staining captures a snapshot of those cells in which calpain-2 was activated precisely at the time-point of fixation. Another reason might be that calpain-2 is inactivated very quickly via autolysis [ 47 , 48 ], which might lead to only small amounts of CMAC being cleaved by calpain-2. Further co-staining experiments, including with other calpain isoforms and other signaling molecules involved in cGMP-dependent cell death, could help to unravel the time course of photoreceptor degeneration more precisely.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the calpain activity assay was performed on live retinal explants over a duration of 6 h, whereas calpain-2 staining captures a snapshot of those cells in which calpain-2 was activated precisely at the time-point of fixation. Another reason might be that calpain-2 is inactivated very quickly via autolysis [ 47 , 48 ], which might lead to only small amounts of CMAC being cleaved by calpain-2. Further co-staining experiments, including with other calpain isoforms and other signaling molecules involved in cGMP-dependent cell death, could help to unravel the time course of photoreceptor degeneration more precisely.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of CNGCs depolarizes photoreceptors to the extent that voltage gated Ca 2+ channels (VGCC) in the soma and synapse open [ 97 ]. This results in further Ca 2+ influx that must be extruded by PMCA at the expense of additional ATP and which, otherwise, could lead to the activation of calpain-type proteases, which may promote cell destruction [ 98 , 99 , 100 ]. Accordingly, the idea that high Ca 2+ may be responsible for cell death [ 48 ], and by extension for photoreceptor degeneration [ 101 ], has motivated several studies attempting to block either CNGC or VGCC for therapeutic purposes.…”
Section: Cgmp-dependent Cell Death In Rdmentioning
confidence: 99%
“…Several recent studies have shown that individual calpain species may serve distinct roles in vivo (Baudry 2019;Franco, Perrin, and Huttenlocher 2004;Santos et al 2012). Furthermore, calpain isoforms show differences regarding the time window of proteolysis, the pattern of autolysis and the concentration of Ca 2+ required for activation (Shinkai-Ouchi et al 2020;Yoshimura et al 1983). Notably, calpain-2 requires 2-3 magnitudes more Ca 2+ compared to calpain-1 to be activated.…”
Section: Calpain-2 Is Activated In the Final Stages Of Photoreceptor Cell Deathmentioning
confidence: 99%